Does Audit Tenure, Audit Firm Size, Audit Fee, and Competence Matter? - Roselita Ramadhani Abidin; Ni Nyoman Alit Triani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study investigates and discusses the effect of audit tenure, firm size, audit fees, and competence on audit quality in 2020. The population of this study includes all companies listed on the Indonesia Stock Exchange (IDX) in 2020, with a sample of 535 companies originating from 9 industrial sectors. This study is categorized as a type of quantitative research and uses a selection combined purposive sampling technique, namely collecting samples with specific criteria and cross-sectional data consisting of several related sub-objects simultaneously. Audit quality is proxied by specialist KAP, audit tenure, audit firm size, and competence proxied by dummy, audit fee equal to the honorarium written in the annual report. The analytical techniques used in this study include Descriptive Statistical Analysis, Model Feasibility Test, Overall Model Feasibility Test, Coefficient of Determination Test, and Hypothesis Testing using Logistic Regression Analysis. In this study, audit tenure has a negative effect, audit firm size has a positive impact, and audit fees and competence have no effect on audit quality.